Work Motivation of Soldiers of Batalyon 23 Group-2 Kopassus in Sukoharjo - Lukman Yusudin; Sudarwai; Istiatin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the influence of work environment, compensation, education and career development on the work motivation of soldiers of the 23rd Battalion Group-2 Kopassus in Sukoharjo.This study uses a quantitative method with primary data collection and purposive sampling techniques using multiple linear regression analysis methods. The population in this study is all members of Detachment-1 Battalion-23 Group-2 Kopassus according to the personnel nominative set on October 1, 2023 with a sample of 50 soldiers, both non-commissioned officers and officers. The data analysis techniques used for statistical analysis were multiple linear regression tests, F tests, t tests, and determination coefficients. The results of the study showed that the variables of Work Environment, Compensation, and Career Development had an effect on the work motivation of soldiers of the 23rd battalion group-2 of Kopassus in Sukoharjo but the level of education had no effect on the work motivation of soldiers of the 23rd battalion group-2 of Kopassus in Sukoharjo. The variables of Work Environment, Compensation, Career Development and Education Level contributed to Motivation by 70.5% while the remaining 29.5% was explained by other variables that were not proposed in this study. Suggestions that can be given to Battalion 23 Group 2 Kopassus are expected to conduct regular monitoring and evaluation of the work environment, compensation and performance development because these variables have a significant influence on motivating soldiers. Keywords: Presentation of Financial Statements, Accounting System, Accessibility, Internal Control and Accountability of Regional Financial Management